Measurement tools and indicators for assessing nurturing care for early childhood development: A scoping review - Joshua Jeong; Lilia Bliznashka; Eileen Sullivan; Elizabeth Hentschel; Youngkwang Jeon; Kathleen L. Strong; Bernadette Daelmans (Public Library of Science (PLoS), 2022)
Nurturing care encompasses five components that are crucial for supporting early childhood development: good health, adequate nutrition, opportunities for early learning, responsive caregiving, and safety and security. While there has been increasing attention in global public health towards designing and delivering programs, services, and policies to promote nurturing care, measurement has focused more on the components of health and nutrition, with less attention to early learning, responsive caregiving, and safety and security. We conducted a scoping review to identify articles that measured at least one nurturing care outcome in a sample of caregivers and/or children under-5 years of age in low- and middle-income countries (LMICs). We systematically searched five electronic bibliographic databases for peer-reviewed articles published from database inception until November 30, 2020. We first classified outcomes to their respective nurturing care component, and then applied an inductive approach to organize key constructs within each nurturing care component and the specific measures and indicators used across studies. We identified 239 total articles representing more than 50 LMICs for inclusion in the review. The majority of included studies reported a measure of nutrition (N = 166), early learning (N = 140), and health (N = 102), followed by responsive caregiving (N = 78) and lastly safety and security (N = 45). For each nurturing care component, we uncovered multiple constructs relevant to children under-5: nutrition (e.g., anthropometry, complementary feeding), early learning (e.g., stimulation practices, early childhood education), health (e.g., birth outcomes, morbidity), responsive caregiving (e.g., parental responsivity, parent-child interactions), and safety and security (e.g., discipline, inadequate supervision). Particularly for outcomes of early learning and responsive caregiving, there was greater variability with regards to the measures used, reported indicators, and analytic construction of variables than the other three nurturing care components. This study provides a comprehensive review of the current state of measurement of nurturing care. Additional research is needed in order to establish the most optimal measures and indicators for assessing nurturing care, especially for early learning and responsive caregiving.